Improving Beef Cattle Production in Free Range Systems: Implications for Indonesia - McCosker, Kieren (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
This review describes the relevant herd management practices and policies of northernÂ Australian owners/managers of beef breeding businesses, focusing on those considered to bepotentially applicable for free range beef cattle operations in Indonesia.